Sustainable Tourism at the Edge of Biodiversity: Community Experiences in Indonesia’s Marine Protected Areas - Ahmad Rapsan Jani; Putrawan Habibi; I Gusti Ngurah Oka Widjaya; Yanti Mayasari Ginting (Advances in Tourism Studies, 2025)
Marine protected areas (MPAs) in Indonesia, such as Raja Ampat and Wakatobi, have become internationally recognized for their biodiversity and as ecotourism destinations. While tourism has been promoted as a mechanism to finance conservation and generate local income, little is known about how resident communities perceive and navigate the tensions between ecological protection and livelihood needs. This study employs a qualitative research design to examine community narratives of sustainable tourism within MPAs. Data were collected through ethnographic fieldwork, participant observation, semi-structured interviews with fishermen, homestay owners, and dive guides, as well as focus group discussions with community leaders. Thematic analysis reveals that residents often view tourism as both an opportunity for economic diversification and a source of restrictions on traditional livelihoods, particularly fishing. Narratives highlight ambivalence, as communities’ articulate pride in contributing to global conservation while simultaneously voicing concerns about exclusion, inequitable benefit distribution, and cultural change. The findings underscore that sustainable tourism in MPAs cannot be reduced to visitor management or ecological indicators alone. Instead, it must incorporate local voices and participatory governance to achieve equitable and resilient conservation outcomes.